The Candida albicans-Specific Gene EED1 Encodes a Key Regulator of Hyphal Extension - Sullivan, Derek; Moran, Gary (My University, 2011)
The extension of germ tubes into elongated hyphae by Candida albicans is essential for damage of host cells. The C. albicans-specific gene EED1 plays a crucial role in this extension and maintenance of filamentous growth. eed1? cells failed to extend germ tubes into long filaments and switched back to yeast growth after 3 h of incubation during growth on plastic surfaces. Expression of EED1 is regulated by the transcription factor Efg1 and ectopic overexpression of EED1 restored filamentation in efg1?. Transcriptional profiling of eed1? during infection of oral tissue revealed down-regulation of hyphal associated genes including UME6, encoding another key transcriptional factor. Ectopic overexpression of EED1 or UME6 rescued filamentation and damage potential in eed1?. Transcriptional profiling during overexpression of UME6 identified subsets of genes regulated by Eed1 or Ume6. These data suggest that Eed1 and Ume6 act in a pathway regulating maintenance of hyphal growth thereby repressing hyphal-to-yeast transition and permitting dissemination of C. albicans within epithelial tissues.
PUBLISHED
Keywords: Infectious diseases; Candida albicans; Genes & Society; Immunology, Inflammation & Infection